2019
DOI: 10.1042/bsr20182394
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA H19 promotes corneal neovascularization by targeting microRNA-29c

Abstract: Long non-coding RNA (lncRNA) H19 has been implicated in tumor angiogenesis. However, whether H19 regulates the progression of corneal neovascularization (CNV) is unclear. The present study aimed to determine the function of H19 in CNV and its possible molecular mechanism. Here, we found that the H19 levels were remarkably increased in vascularized corneas and basic fibroblast growth factor (bFGF)-treated human umbilical vein endothelial cells (HUVECs). In vitro, H19 up-regulation promoted proliferation, migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
1
10
1
Order By: Relevance
“…This result seems to be consistent with the idea that lncRNA may be important in maintaining tissue identity [127]. The involvement of lncRNA H19 in neovascularization has recently described with lncRNA H19 acting as a molecular sponge for miR-29c to regulate the expression of VEGF-A [128].…”
Section: Non-coding Rnas In Lymphangiogenesissupporting
confidence: 90%
“…This result seems to be consistent with the idea that lncRNA may be important in maintaining tissue identity [127]. The involvement of lncRNA H19 in neovascularization has recently described with lncRNA H19 acting as a molecular sponge for miR-29c to regulate the expression of VEGF-A [128].…”
Section: Non-coding Rnas In Lymphangiogenesissupporting
confidence: 90%
“…In the present study, H19 was downregulated in the dermal fibroblast exposure to FGF2, suggesting FGF2 attenuated the expression of H19. Conversely, Sun et al reported the H19 levels were remarkably increased in FGF2-treated human umbilical vein endothelial cells (Sun et al 2019). Thus, our study indicated the FGF2-mediated H19 expression appeared to exhibit a context-dependent pattern.…”
Section: Discussioncontrasting
confidence: 51%
“…In the present study, H19 was downregulated in the dermal fibroblast exposure to FGF2, suggesting FGF2 attenuated the expression of H19. Conversely, Sun et al (2019) reported the H19 levels were remarkably increased in FGF2-treated human umbilical vein endothelial cells. Thus, our study indicated the FGF2-mediated H19 expression appeared to exhibit a context-dependent pattern.…”
Section: Discussionmentioning
confidence: 96%